Performance Evaluation of Construction Projects Based on Identified and Clustered Barriers Using Data Envelopment Analysis: a Case Study of Projects of Execution Department of Bonyad Maskan Chaharmahal and Bakhtiari Province - Marziyeh Fatahi Nafchi; Hadi Shirouyehzad (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The present study aims to evaluate the performance of construction projects based on identified and clustered implementation barriers using data envelopment analysis.Methodology: This research has focused on identifying the implementation barriers of civil engineering projects by examining previous studies. Identifying the implementation barriers of civil engineering projects enables assessing the importance and performance of each barrier using a two-way questionnaire during project execution. This research clustered the data collected through the two-way questionnaire. Clustering was used to facilitate solving the data envelopment analysis model. The performance evaluation of the implementation of each studied project was carried out using the data envelopment analysis method.Findings: In this study, individual projects were evaluated using a questionnaire on implementation barriers of civil engineering projects, and efficient and inefficient projects were identified.Originality/Value: This research can provide more comprehensive information on the performance of implementing civil engineering projects by identifying implementation barriers. With this accurate information, the success of projects can be measured against each other, and decisions can be made more efficiently to address weaknesses and strengthen strengths. This research evaluates the performance of civil engineering projects with information on the implementation barriers of these projects. Thus, performance evaluation will lead to desirable outcomes in the execution of future projects.